2018
DOI: 10.1111/echo.14096
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional transesophageal echocardiography vs cardiac magnetic resonance in the assessment of planimetric mitral valve area in rheumatic mitral stenosis

Abstract: For the diagnosis and the follow-up of rheumatic MS, planimetric CMR MVA is an alternative noninvasive method which highly correlates with planimetric 3D TEE MVA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…In practice, decision making usually relies on direct planimetry of MVA (6). In the present study, in line with previous studies (712), high agreement was observed between MVA obtained by CMR and 2D TTE, with 95% limits of agreement ± 0.24 cm 2 , i.e. the expected difference between the two methods if applied for the same subject will be <0.24 cm 2 in 95% of cases.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In practice, decision making usually relies on direct planimetry of MVA (6). In the present study, in line with previous studies (712), high agreement was observed between MVA obtained by CMR and 2D TTE, with 95% limits of agreement ± 0.24 cm 2 , i.e. the expected difference between the two methods if applied for the same subject will be <0.24 cm 2 in 95% of cases.…”
Section: Discussionsupporting
confidence: 92%
“…MVA by CMR in our study was closer to 2D than 3D echocardiography, and the agreement between CMR and 3D echocardiography was slightly lower than that with 2D echocardiography, with significant differences between CMR and each of 3D TTE and TEE, indicating overestimation of the MVA by CMR in comparison to 3D echocardiography. Only one previous study compared MVA by CMR and 3D TEE, and reported similar limits of agreement to our study, with slightly larger MVA values by CMR than 3D TEE (8).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Mitral valve area (MVA) is technically measured by two-dimensional (2D) planimetry with high precision to assess the severity of mitral pathological changes, such as stenosis (1). However, the improvement of imaging methods using three-dimensional techniques has been considered in some studies to achieve the accurate values of these changes and minimize diagnostic errors (especially in the presence of distorted valvular tip or poor echo widow) (2). The application of three-dimensional (3D) methods, such as real-time 3D echocardiography significantly reduced the possibility of mitral stenosis over-estimation due to accurate geometric assessment of valve dimensions and details of ischemic or rheumatic valvular changes with high resolution (3)(4).…”
Section: Introductionmentioning
confidence: 99%